2002
DOI: 10.1016/s0002-9440(10)64926-7
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking Smad3 Are Protected Against Cutaneous Injury Induced by Ionizing Radiation

Abstract: Transforming growth factor-beta (TGF-beta) plays a central role in the pathogenesis of inflammatory and fibrotic diseases, including radiation-induced fibrosis. We previously reported that mice null for Smad3, a key downstream mediator of TGF-beta, show accelerated healing of cutaneous incisional wounds with reduced inflammation and accumulation of matrix. To determine if loss of Smad3 decreases radiation-induced injury, skin of Smad3+/+ [wild-type (WT)] and -/- [knockout (KO)] mice was exposed to a single dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
232
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 265 publications
(256 citation statements)
references
References 64 publications
20
232
1
3
Order By: Relevance
“…64 Exposure of these mice to radiation-induced injury causes significantly less epidermal acanthosis and dermal influx of mast cells, macrophages, and neutrophils than wild type littermates, demonstrating that these mice have a significantly reduced fibrotic response. 65 Smad4 mice present with inflammatory polyps in the glandular stomach and duodenum consistent with previous reports that Smad4 mutations are involved in a subset of familial juvenile polyposis. 66…”
Section: Tgf-β Knockout Micesupporting
confidence: 92%
“…64 Exposure of these mice to radiation-induced injury causes significantly less epidermal acanthosis and dermal influx of mast cells, macrophages, and neutrophils than wild type littermates, demonstrating that these mice have a significantly reduced fibrotic response. 65 Smad4 mice present with inflammatory polyps in the glandular stomach and duodenum consistent with previous reports that Smad4 mutations are involved in a subset of familial juvenile polyposis. 66…”
Section: Tgf-β Knockout Micesupporting
confidence: 92%
“…15 The downstream signaling effects of TGF-b are mediated by Smad3. 16 The Smad3 loss can afford protection from radiation-induced fibrosis, 17 bleomycin-induced pulmonary fibrosis, 18 presumably by interrupting the pathways leading up to matrix production by fibroblasts that lead to tubulointerstitial fibrosis. Recent reports indicate that Smad7 is selectively decreased, whereas phosphorylation of Smad2 and Smad3 is increased in UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…9 -11), whereas Smad3-mediated TGF␤ signaling is a major culprit in suppressing Prdx6 expression in this scenario. It has been reported that mice lacking Smad3 show accelerated healing (15,89) and has been suggested that Smad3 plays a crucial role in tissue repair during injury (90). Importantly, recently, several reports have come forward documenting the role of PRDX6 in wound healing and in maintaining cell/tissue integrity (24).…”
Section: Discussionmentioning
confidence: 99%